Figure-It-Out Function! - Part 3: The Powers of Factorials

Algebra Level 4

Let there be a function f ( x ) : Z Z f(x):\mathbb{Z}\rightarrow \mathbb{Z} with the following conditions

{ f ( x + 1 ) = f ( x ) + ( f ( x ) ) ! f ( 3 ) = 28 \begin{cases}{f(x+1)=f(x)+(f(x))!} \\ {f(3)=28}\end{cases}

Evaluate i = 1 4 [ f ( i ) f ( 3 i ) ] \displaystyle \sum_{i=-1}^{4} \left [ f(i) \cdot f(3-i) \right ]

This problem is part of the Figure-It-Out Function! series.


The answer is 72.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Shivamani Patil
Aug 17, 2014

Now let x = 2 x=2

Therefore f ( 3 ) = f ( 2 ) + ( f ( 2 ) ) ! f(3)=f(2)+(f(2))!

Now it is interesting to note that f ( 3 ) = 28 = 4 + 4 ! f(3)=28=4+4!

Therefore 4 + 4 ! = f ( 2 ) + ( f ( 2 ) ) ! 4+4!=f(2)+(f(2))!

By comparing

we get f ( 2 ) = 4 f(2)=4 ...... 1 1

Now let x = 1 x=1

Therefore we get f ( 2 ) = f ( 1 ) + ( f ( 1 ) ) ! f(2)=f(1)+(f(1))!

2 + 2 ! = f ( 1 ) + ( f ( 1 ) ) ! 2+2!=f(1)+(f(1))!

Again by comparing we get f ( 1 ) = 2 f(1)=2

By continuing above process we get f ( 0 ) = 1 f(0)=1 ..... 2 2

By condition we get f ( 1 ) = 0 f(-1)=0 ...... 3 3

That summation is equal to 2 [ f ( 1 ) f ( 4 ) + f ( 1 ) f ( 2 ) + f ( 0 ) f ( 3 ) ] 2[f(-1)f(4)+f(1)f(2)+f(0)f(3)]

By condition f ( 4 ) = 28 + 28 ! f(4)=28+28!

But we don't need to evaluate it

Therefore summation equals 2 [ 0 + 8 + 28 ] 2[0+8+28]

i.e 72 72

great problem man.................keep it up............

Gaurav Kashyap - 6 years, 9 months ago

Very good problem which requires logical thinking.

shivamani patil - 6 years, 10 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...